Metode Total Physical Response dalam Peningkatan Keterampilan Berbicara Bahasa Jerman - Nuraisyah, Andi; Saleh, Nurming (Universitas Negeri Makassar, 2025)
Abstract. This study aims to improve the German speaking skills of Class XI.1 Students of SMA Negeri 24 Bone Regency using the Total Physical Response method. This study is a classroom action research (CAR) which includes planning, implementation, observation and reflection. The subjects of this study were 33 class XI.1 students. The data collection techniques used were speaking skills tests and observations. The results of the first cycle observation, the teacher had not applied the Total Physical Response method according to the steps, so that students were not yet fluent in speaking German, the results still did not reach the qualifications. However, the results obtained in cycle II, all steps of the Total Physical Response method had been implemented well and students were able to speak German clearly and fluently. Quantitative data were obtained through speaking skills tests in cycles I and II. The results of the students' German speaking test in cycle I obtained an average of 70.41 and increased in cycle II with an average value of 81.75. The results of this study indicate that the application of the Total Physical Response method can improve the German speaking skills of class XI.1 students of SMA Negeri 24 BoneKeywords: Classroom Action Research, Speaking Skills, Total Physical Response